Advanced analysis in steel frame design : guidelines for direct second-order inelastic analysis - Surovek, Andrea Eden, 1965- (American Society of Civil Engineers, 2012)
Prepared by the Special Project Committee on Advanced Analysis of the Technical Committee on Structural Members of the Structural Engineering Institute of ASCE. This report presents formal guidelines for the use of second-order inelastic analysis in the design and assessment of steel framing systems. This advanced analysis methodology focuses on the strength of the structural system as a whole, rather than the design load levels producing the first member failure. The report includes design rules, background and commentary regarding the rules, and benchmarks for columns and frames. It provides specific recommendations regarding the rigor of analysis, minimum modeling requirements, consideration of limit states, serviceability, and live load reduction, yet allows latitude for the judgment of the design engineer. The recommendations presented in this report will be particularly valuable to structural engineers, specification developers, and developers of structural analysis software.
Keywords: Elastic analysis (Engineering); Structural design.; Steel framing (Building) -- Design and construction.; elektronické knihy; electronic books